Genetic resistance to curtobacterium flaccumfaciens pv. flaccumfaciens in bean genotypes - de Souza, Valmir Luiz [UNESP] (2006)
Curt obact eri um f l accumf aci ens pv. f l accumf aci ens ( Cff ), the causal agent of t he bacter i al wi l t of common bean ( Phaseol us vulgaris), is a vascular pathogen of difficult control. The disease was first detected in Brazil 1995, in São Paulo State. Due to the difficulty i n cont rol l i ng t hi s di sease, genet i c resi st ance has been t he bet t er option. The aim of this study was to evaluate the reaction of common bean genot ypes t o t he bact eri al wi l t, i n 333 accesses of t he bean plant germplasm database of the Instituto Agronômico de Campinas (IAC). Highly resistant and susceptible bean genotypes were selected for the observation of Cff colonization in the xylem vessel by scanning electron microscopy. The results of the screening for genetic resistance in 333 genotypes indicated variability in relation to a Cff Feij 2634 isolate. The materials were classified into 4 resistance level groups: 29 highly resistant genotypes (8.7%), 13 resistant genotypes (3.9%), 18 moder at el y r es i s t ant genot ypes ( 5%) and 273 s us cept i bl e genotypes (81%). From these results, about 18% of the genotypes – ranging from highly to moderately resistant – may be useful for the genetic breeding program as a source of resistance genes for Cff. Using scanning electron microscopy, xylem vessels of highly resistant genotypes presented a number of bacterial agglutinations involved by filaments and tangled structures under punctuations of the xylem vessel wal l not obser ved i n suscept i bl e genot ypes, suggest s t he act i vat i on of st r uct ur al and bi ochemi cal def ense mechani sms i n resistant plants.